Direct Z‑Scheme Water Splitting Photocatalyst Based on Two-Dimensional Van Der Waals Heterostructures - Zhang, Ruiqi; Zhang, Lili; Zheng, Qijing; Gao, Pengfei; Zhao, Jin; Yang, Jinlong (The journal of physical chemistry letters, 2018)
Mimicking the natural photosynthesis in plants, Z-scheme water splitting is a promising strategy to improve photocatalytic activity. Searching for the direct Z-scheme photocatalysts is urgent and the crucial factor for the photocatalytic efficiency is the photogenerated electron–hole (e–h) recombination rate at the interface of two photosystems. In this report, based on time-dependent ab initio nonadiabatic molecular dynamics (NAMD) investigation, we first report a two-dimensional (2D) metal-free van der Waals (vdW) heterostructure consisting of monolayer BCN and C2N as a promising candidate for direct Z-scheme photocatalysts for water splitting. It is shown that the time scale of e–h recombination of BCN/C2N is within 2 ps. Among such e–h recombination events, more than 85% are through the e–h recombination at the interface. NAMD simulations based on frozen phonon method prove that such an ultrafast interlayer e–h recombination is assisted by intralayer optical phonon modes and the interlayer shear phonon mode induced by vdW interaction. In these crucial phonon modes, the interlayer relative movements which are lacking in traditional heterostructures with strong interactions, yet exist generally in various 2D vdW heterostructures, are significant. Our results prove that the 2D vdW heterostructure family is convincing for a new type of direct Z-scheme photocatalysts searching.